Strength And Compressibility Characteristics Of Amorphous Tropical Peat - Akeem, Gbenga Amuda; Alsidqi, Hassan; Dayang Norfaranina, Datu Unoi; Siti Noor Linda, Binti Taib (Taiwan Geotechnical Society, 2019)
ABSTRACT Peat is viewed to deflect from the standard guidelines of soil behaviours due to the influence of structural fibres and high compressibility. Hence, the laboratory strength behaviour of peat is often complex, and the geotechnical test results may be doubtful. Amorphous peat is expected to behave differently since the fibres have been broken down into smaller organic contents and humus material. Laboratory tests such as scanning electron microscopy (SEM), one-dimensional (1D) oedometer tests and isotropically consolidated undrained (CIUC) triaxial tests were conducted on amorphous peat samples obtained from a site in Kota-Samarahan, Malaysia. The microstructure of amorphous peat indicates colloidal amorphous-granular particles with no visible evidence of hollow cellular connections. The measured compressibility and strength properties reflect the effect of decomposition and are somewhat different from that of fibrous peat. Interestingly, the strain hardening characteristic which complicates the interpretation of strength results is less significant, and the tension cutoff line is not reached. Based on the outcome of this study, strength and settlement behaviour of amorphous peat can be reasonably measured in the laboratory for design and construction of highways, embankments and other infrastructures.